Severity of Premenstrual Symptoms Predicted by Second to Fourth Digit Ratio - Kaneoke, Yoshiki; Donishi, Tomohiro; Iwahara, Akihiko; Shimokawa, Toshio (Frontiers in Medicine, 2017)
Women of reproductive age often experience a variety of unpleasant symptoms prior to the onset of menstruation. While genetics may influence the variability of these symptoms and their severity among women, the exact causes remain unknown. We hypothesized that symptom variability originates from differences in the embryonic environment and thus development caused by variation in exposure to sex hormones. We measured the second to fourth digit ratios (2D:4D) in 402 young women and investigated the potential relationships of this ratio premenstrual symptoms using a generalized linear model. We found that two models (one with two predictors such as both hands’ digit ratios and the other with the difference between the two digit ratios, Dr-l) were significantly different from the constant model as assessed by chi-square test. The right digit ratio and Dr-l were negatively related to the symptom scores, and the left digit ratio was related to the scores. When premenstrual symptoms were classified into 8 categories, 5 categories, including pain, concentration, autonomic reaction, negative affect, and control were associated with the digit ratios and Dr-l. Behavioral changes, water retention were not predicted by them. Arousal was predicted by Dr-l. The right 2D:4D is thought to be determined by the balance of testosterone and estrogen levels during early embryogenesis and is not affected by post-partum levels of sex hormones, while the left 2D:4D might be affected by the other prenatal environmental factors. We conclude that the embryonic environment, including the relative concentration of sex hormones an embryo is exposed to is associated with the severity of premenstrual symptoms once menarche is reached.